Hubungan Pengetahuan Dan Sikap Remaja Dengan Penggunaan Kosmetik Pencerah Wajah Yang Legal - Haryati Lubis, Vebry; Sugiyono, Sugiyono; Saputri, Adhellia Ika (STIKes IMC Bintaro, 2023)
Background: In 2018, BPOM found illegal cosmetics, which were dominated by cosmetic products containing mercury, hydroquinone and retinoic acid. Use of illegal cosmetics can cause irritation, photosensitization, allergies, acne, physical obstruction, brain and kidney damage, fetal problems, lung failure and cancer. Objective: To find out the relationship between knowledge and attitudes of adolescents with the use of legal facial lightening cosmetics. Method: This type of research is a quantitative approach cross sectional. The sampling technique issimple random sampling. The sample in this study were 50 level 1 students at STIKes IMC Bintaro who filled out the questionnaire. Data were analyzed univariate and bivariate(chi-square). Results: most of the respondents had less knowledge (70.0%) and less attitude (60.0%). Conclusion: There is a significant relationship between knowledge and the use of legal face lightening cosmetics (p=0,002). and there is a relationship between adolescent attitudes and the use of legal face brightening cosmetics (p=0,000). Suggestion: Expect teenagerscan better understand the use of lightening cosmetic products that are safe to use and the importance of knowledge about cosmetic products in order to avoid the negative side effects of using lightening cosmetics.